Development of Theoretical Study of Social Interpretation (Social Relations) - Gagah Daruhadi (Journal of World Science, 2024)
This reserach explores the application of Qur'anic social interpretation in social relations to address the complexity of contemporary social issues. This research aims to bridge the understanding of the Qur'anic teachings with their application in daily social dynamics, given the urgency of increasing social problems. Using a qualitative content analysis method, this study identifies and explains various social interpretations, evaluates their relevance in the modern social context, and examines the methodological differences between classical and contemporary interpretive approaches. The research focuses on the historical development of social tafsir, the influence of important figures such as Al-Sayyid Jamaluddin al-Afghani and Muhammad 'Abduh, and the application of tafsir in the context of multiculturalism and social justice. The results of this study are expected to produce strategies to promote social harmony through the application of inclusive and adaptive tafsir. The implications of the research show that a more inclusive understanding and application of social tafsir can be a solution in facing modern social challenges.